2018
DOI: 10.1037/pas0000558
|View full text |Cite
|
Sign up to set email alerts
|

The Online Social Support Scale: Measure development and validation.

Abstract: A new measure, the Online Social Support Scale, was developed based on previous theory, research, and measurement of in-person social support. It includes four subscales: Esteem/Emotional Support, Social Companionship, Informational Support, and Instrumental Support. In college and community samples, factor analytic and item response theory results suggest that subtypes of in-person social support also pertain in the online world. Evidence of reliability, convergent validity, and discriminant validity provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 77 publications
4
87
0
1
Order By: Relevance
“…These findings reflect existing research on the distinctions between FTF and SM-based support in general and their associations with mental health, although the associations found in our study appear to be smaller in magnitude (McCloskey et al, 2015;Teo et al, 2019). However, our findings differ from some prior studies that showed that like FTF emotional support, online support was associated with lower depression (Grieve et al, 2013;Nick et al, 2018).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These findings reflect existing research on the distinctions between FTF and SM-based support in general and their associations with mental health, although the associations found in our study appear to be smaller in magnitude (McCloskey et al, 2015;Teo et al, 2019). However, our findings differ from some prior studies that showed that like FTF emotional support, online support was associated with lower depression (Grieve et al, 2013;Nick et al, 2018).…”
Section: Discussionsupporting
confidence: 56%
“…One study suggested that SM connectedness may be a distinct yet related construct to FTF connectedness, and that SM connectedness may be associated with lower depression (Grieve et al, 2013). Additionally, a formal scale development study found that like FTF social support, online (i.e., gaming and dating sites, texting, and social media platforms) social support was protective against depression-related outcomes, although to a slightly lesser degree (Nick et al, 2018). However, another study found that while increased frequency of FTF social contact was associated with lower odds of depression, increased social interaction on SM was not (Teo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Evidence spanning decades suggests that although such groups are also widely used in illness contexts, and may have benefits for individuals such as some patients and family caregivers, 3234 the links to psychological and physical wellbeing remain largely unclear and underexplored, 3539 an issue perhaps in part complicated by the absence of appropriate measurement instruments linking online networks and interactions to health. 40…”
Section: Introductionmentioning
confidence: 99%
“…While online social environments are increasingly explored in the literature, such research generally utilizes ad hoc scales (which typically have weak or unknown psychometric properties), 40 or measures developed for offline contexts. While online social interactions mirror their offline counterparts in some ways, there are also many fundamental differences, 59 such that offline measures may not be suitable for or relevant to online work, underscoring the need for development of a measure specific to online contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Components of Social Support of Nursing Students Defined in the Fieldwork Stage Daily contact with family, professors, school friends, seniors and juniors, and occasional contact with friends outside of school or hometown friends ://doi.org/10.4094/chnr.2020 26…”
mentioning
confidence: 99%